2019
DOI: 10.1186/s12879-019-4546-6
|View full text |Cite
|
Sign up to set email alerts
|

The clinical features and prognosis of infective endocarditis in the elderly from 2007 to 2016 in a tertiary hospital in China

Abstract: BackgroundInfective endocarditis (IE) especially in the elderly is a serious disease, with a worse prognosis.MethodsA retrospective cohort study was conducted. A total of 405 patients with definite IE were divided into three groups: 205 patients under 50 years old, 141 patients between 50 and 64 years old and 59 patients over 65 years old.ResultsFor older patients, clinical symptoms such as fever, anemia, and heart murmur were as common as the younger patients. IE in old patients had more frequent nosocomial o… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
37
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(45 citation statements)
references
References 27 publications
1
37
0
6
Order By: Relevance
“…Contrasting study findings may also reflect inconsistent definitions of 'elderly', which can range from over 65 years to over 70 years. [10][11][12][13][14][15][16][17] To the best of our knowledge, the present study is one of the largest to focus on IE among very elderly patients. The large sample enabled us to comprehensively investigate the characteristics of IE among very elderly patients in a clinical setting.…”
Section: Discussionmentioning
confidence: 89%
See 3 more Smart Citations
“…Contrasting study findings may also reflect inconsistent definitions of 'elderly', which can range from over 65 years to over 70 years. [10][11][12][13][14][15][16][17] To the best of our knowledge, the present study is one of the largest to focus on IE among very elderly patients. The large sample enabled us to comprehensively investigate the characteristics of IE among very elderly patients in a clinical setting.…”
Section: Discussionmentioning
confidence: 89%
“…12 Several studies have reported the similarities and the differences of IE among elderly compared with non-elderly patients, some of which showed the conflicting result regarding clinical characteristics such as causative microorganisms and echocardiographic findings. [10][11][12][13][14][15][16][17] This contradiction may be explained by the diversity in health conditions across elderly people. Ageing is a highly variable process characterised by a wide spectrum of conditions: some aged individuals are healthy whereas others are bedridden.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[4][5][6][7][8][9] Em pacientes da terceira idade com EI, existem diferenças quanto a apresentação clínica, complicações, presença de comorbidades, abordagem terapêutica e mortalidade. 4,[10][11][12][13] Diretrizes de EI não abordam especificamente idosos e não está claro até que ponto elas podem ser utilizadas de maneira adequada nesses pacientes. 2,14,15 A população idosa claramente beneficiou-se do progresso médico, com técnicas diagnóstico-terapêuticas que influenciam no aumento da expectativa de vida e em procedimentos menos invasivos.…”
Section: Introductionunclassified